Feasibility study of a randomised controlled trial of preoperative and postoperative nutritional supplementation in major lung surgery - Amelia Swift; Sebastian T Lugg; Babu Naidu; Nikolaos Efstathiou; Amy Kerr; Hazem Fallouh; Maninder Kalkat; Richard Steyn; Salma Kadiri; Ehab Bishay; Krishna Kholia; Venessa Rogers (BMJ Open)
Objectives Malnutrition and weight loss are important risk factors for complications after lung surgery. However, it is uncertain whether modifying or optimising perioperative nutritional state with oral supplements results in a reduction in malnutrition, complications or quality of life.Design A randomised, open label, controlled feasibility study was conducted to assess the feasibility of carrying out a large multicentre randomised trial of nutritional intervention. The intervention involved preoperative carbohydrate-loading drinks (4×200 mL evening before surgery and 2×200 mL the morning of surgery) and early postoperative nutritional protein supplement drinks two times per day for 14 days compared with the control group receiving an equivalent volume of water.Setting Single adult thoracic centre in the UK.Participants All adult patients admitted for major lung surgery. Patients were included if were able to take nutritional drinks prior to surgery and give written informed consent. Patients were excluded if they were likely unable to complete the study questionnaires, they had a body mass index <18.5 kg/m2, were receiving parenteral nutrition or known pregnancy.Results All patients presenting for major lung surgery were screened over a 6-month period, with 163 patients screened, 99 excluded and 64 (41%) patients randomised. Feasibility criteria were met and the study completed recruitment 5 months ahead of target. The two groups were well balanced and tools used to measure outcomes were robust. Compliance with nutritional drinks was 97% preoperatively and 89% postoperatively; 89% of the questionnaires at 3 months were returned fully completed. The qualitative interviews demonstrated that the trial and the intervention were acceptable to patients. Patients felt the questionnaires captured their experience of recovery from surgery well.Conclusion A large multicentre randomised controlled trial of nutritional intervention in major lung surgery is feasible and required to test clinical efficacy in improving outcomes after surgery.Trial registration number ISRCTN16535341.